Reasoning ability through challenge based learning kahoot - Wati Susilawati; Kartika Dewi (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2019)
The main objective is to analyze the improvement of mathematical reasoning ability through the challenge based learning with kahoot application. An experimental study, pre-test and post-test control group design. The population subjects were all students of class XI of the SMAN 26 Bandung, by involving a sample of three classes through random sampling techniques from five parallel classes available. Instrument for mathematical reasoning tests. Findings: There was improvement in mathematical reasoning abilities of students who obtained a challenge based learning assisted by the kahoot application, challenge based learning without a kahoot, and conventional learning. Improvement of mathematical reasoning abilities of students who obtained a challenge based learning with kahoot application is better than challenge based learning without the kahoot, and expository learning. Challenge based learning kahoot applications can facilitate conflict processes, discovery, social interaction, and reflective to improve students’s mathematical reasoning abilities.